Development Material Learning for Writing Poem by using Lotus Technique to 10th grade of Senior High School Students in MAS Tahfizil Qur’an Medan - Nurul Kusuma Wardani Hutasuhut; Abdurrahman Adisaputera; Isda Pramuniati (BIRCU, 2020)
The aim of this research is to create a teaching material and method in writing poetry using lotus techniques. This research also uses research and development methods. It is research that produces certain products and the effectiveness of their use. The product that will be produced in this research is in the form of poetry writing teaching materials developed with lotus techniques for 10th grade of Senior High School students in MAS Tahfizil Medan. The results of this study indicate that 10th grade students need new methods and teaching materials in improving their understanding in writing poetry. And after testing the lotus technique is very efficient to improve students' ability to write poetry. After the posttest and pretest results the results obtained are the low category by 3.33%, the medium category by 93.34%, and the high category by 3.33%.